2014
DOI: 10.1210/jc.2013-4088
|View full text |Cite
|
Sign up to set email alerts
|

Refining Calcium Test for the Diagnosis of Medullary Thyroid Cancer: Cutoffs, Procedures, and Safety

Abstract: Gender-specific bCT and sCT cutoffs for the identification of C-cell hyperplasia and/or MTC have been defined. The bCT and sCT were found to have a similar accuracy, indicating that serum CT assays with improved functional sensitivity may likely decrease the relevance of the stimulation test in several conditions. Finally, systematic cardiac monitoring confirms the safety of the Ca test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 18 publications
7
69
0
4
Order By: Relevance
“…An alternative method represents the calcium stimulation test, being described as sensitive as well, however, also having (potentially life threatening) side effects 17, 18. Additionally, cut‐offs for the calcium stimulation test are not yet well defined 19. All in all, a simple, safe and reliable complementary or alternative test to CT is warranted to increase the efficacy of a screening programme of thyroid nodules for MTC.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method represents the calcium stimulation test, being described as sensitive as well, however, also having (potentially life threatening) side effects 17, 18. Additionally, cut‐offs for the calcium stimulation test are not yet well defined 19. All in all, a simple, safe and reliable complementary or alternative test to CT is warranted to increase the efficacy of a screening programme of thyroid nodules for MTC.…”
Section: Introductionmentioning
confidence: 99%
“…The thresholds for calcium stimulated Ct levels were > 544 and > 79 pg/mL in males and females, respectively [22]. In this study, the basal serum thresholds for PCt were defined as > 0.5 ng/mL (reference: 0.00 -0.50 ) and the threshold for calcium stimulated abnormal PCt levels were arbitrarily defined as three times the upper limit of normal plus the value for coefficient of variation ( > 1.65 ng/mL).…”
Section: Calcium Stimulation Testmentioning
confidence: 91%
“…The basal serum Ct level thresholds for the identification of MTC were defined as > 68 and > 26 pg/mL in males and females, respectively [22]. The thresholds for calcium stimulated Ct levels were > 544 and > 79 pg/mL in males and females, respectively [22].…”
Section: Calcium Stimulation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcium stimulation test can be used as an alternative (32) (B). Nevertheless, recent studies have shown that with the improved sensitivity of the new assays, both basal and stimulated calcitonin have similar accuracy, which reduces the relevance of the stimulation tests in multiple conditions (33) …”
Section: Recommendationmentioning
confidence: 99%